A Dillema of a Post-Feminist Woman: A Study Case of One Indian Girl - nirmalawati, widya (Universitas Swadaya Gunung Jati, 2018)
After post-feminism period, women still have to struggle to be “perfect human being”as her own ideal. It is not only the case for women having no power, intellectualism, and money, but also for ladies with authority and prosperity enabling her own to be an single individual with financial and time freedom. This can be seen in a contemporary literary work, One Indian Girl (Bhagat: 2016), in which an Indian girl having a prestigious position in an American investment bank could not achieve her ideal life. This paper is aimed to reveal the dilemma of a feminist woman in her relation to men and to her family norms and her defeat to the true reality she failed to mediate. Using post-feminist approach, this paper investigated the fictional facts to prove that source of the problems is actually her female being. It is indicated that the problems she had in her life coming from her female feminist. From the very first, it was depicted that she was viewed negatively by her own mother for being a female baby. Her intellectual is not worthy for boys and her mother. In her study, she was blamed for having her master, rather than early marriage. Finally, she was being accused of earning a lot of money, which normally becomes a prestigious achievement for men, by her boyfriend and her mother. She was in dilemma to choose between her dreamed profession or her marriage. The girl is a character who highly likely to represent other girls or women who are still defeated by the inequities of positioning a man-woman parallelism. Key words: One Indian Girl, post-feminist, dilemma